HUBUNGAN ANTARKOMPONEN MIKROFASIES LERENG TERUMBU OAN CEKUNGAN LOKAL TERUMBU BELAKANG BATUGAMPING BIOKLASTIKA FORMASI BATURAJA 01 OAERAH SEKITAR MUARAOUA, SUMATERA SELATAN - Maryanto, sigit (Jurnal Geologi dan Sumberdaya Mineral, 2008)
Bioclastic limestone of the Baturaja Formation cropping out in the Muaradua area, South Sumatera, is a good research object for microfacies analysis. Polarized microscopic study has revealed that the, bioclastic, limestones are predominantly reef-flank and local back-reef basin deposits. The results of T, F, and P tests of the limestones show a significant difference in their carbonate and terrigenous grains, as well as in their neomorphic materials between the deposits. On the other hand, their matrices, cements, and porosities are of no significant difference. Keywords: reef-flank, back-reef, carbonate grains, petrography